Do ensino público ao ensino privado: uma análise da Escola Santa Terezinha em Ibiá-MG (1937 a 1959) - Souto, Adilour Nery (2012)
This research is inserted in the area of History and Historiography of Education. It is associated with the historical context and the relationship circumstances between public and private schools in Ibiá-MG, by analyzing the process of creation of Santa Terezinha private school. It is a study of the dynamic movement that involved the debate on the democratization of the elementary education in Alto Paranaíba (Ibiá-MG), as well as disputes and consensuses that followed the structure and spread of educational public and private institutions in Brazil, from 1937-1959. The period is from the 1937 Constitution, when Santa Terezinha school was created in Ibiá, and 1959 when of the change in the by-law of the school converging with a time of great political-ideological excitement between the public and private initiative throughout the country. The overall objective was to analyze the relationship of the elementary teaching, represented by Dom José Gaspar School, and the private sector represented by Santa Therezinha School, in order to conduct an inventory of their historical forms of expression, observing the relationships between those two sectors of teaching. We interpreted the interaction limits and conflicts between the public and private schools, throughout the process of institutionalization of education in Brazil. The study had as principle the political, economic and socio-cultural realities constructed in that period. We tried to understand the schooling process in Brazil, particularly in Minas Gerais, as part of the society formed in that period. The heuristics included quantitative and qualitative data obtained from documentary, oral, and iconographical sources that were subject to explanatory analyzes anchored on the dialectical method. Data revealed that while in the national level the political-ideological debate had been strong between the public and private education, in the local universe the agreement between the two schools reflects the political patronage in Brazil. So those two schools, although antagonistic in essence, integrate each other configuring both a relationship of conflict and complement.